Mariana Coelho e a educação das mulheres: uma escritora feminista no campo intelectual (1893-1940) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This thesis aims to investigate Mariana Coelho’s trajectory, notably the period between 1893 to 1940, with the intent to analyze her formation process as a reader and writer, as well as her presence in the intellectual field. Her initial outline, 1893, is associated to her first poem published by Revista Azul, and 1940 highlights the moment in which she ceased to act on public life with her edition of the work Cambiantes and her last letter written to feminist Bertha Lutz. The justification for this investigation is associated to the place occupied by Coelho in the literary, intellectual and feminist scenario of Brazilian/Paranaense history, since both the occupied and taken positions allow for the problematization of her actions in the reading and writing universe, in an attempt to comprehend the strategies which gave way to her entry in the literary and intellectual field, allowing her acknowledgement as an intellectual who strived to educate women so they would have more autonomy and space in their public and professional lives. This paper is supported by sources, some of which are unprecedented, such as correspondences exchanged with leader Bertha Lutz, between 1923 to 1940, as well as reading notes, articles and works periodically published throughout Coelho’s trajectory, in addition to the theoretical-methodological propositions of the sociologist Pierre Bourdieu and the inputs of intellectual history, which allow the comprehension of the cultural and social spaces where Mariana Coelho has gone through, as well as to explain the process which led to the transformation of strategies applied to the social world in order to enter in the intellectual and literary field, in favor of her debate of defense of the feminist cause. In the course of analysis, topics of discussion include Mariana Coelho’s family origins, focusing on her reading formation, during which time she lived in Portugal, understood as a space of social practice and gathering of cultural capital, in addition to describing the process of her departure from Portugal and her arrival in Brazil. Moreover, it is presented how her writing formation, along with her insertion in the Paranaense literary field occurred, highlighting the relationships established with other agents in addition to the positions taken in this social space. It is also evidenced how her feminist conception was shaped and how it structured itself throughout the years through the reading, along with the actions and the relationships established with other feminists, particularly with Bertha Lutz, with whom Coelho kept a relationship known for its friendship bonds, its constant exchange of ideas, as well as disagreements. Finally, by showing the gathering of her cultural capital (her reader and writer status) and her symbolic capital (her ties with several cultural leaderships), it sustains the idea that Mariana Coelho converted these elements into empowering strategies to defend within the intellectual Brazilian/Paranense field, her feminism by conviction, which would envision an educational standard committed to the emancipation of women.
Keywords: Mariana Coelho; Trajetória intelectual; Campo literário e intelectual; Educação e emancipação feminina; Mariana Coelho; Intellectual trajectory; Literary and intellectual field; Female education and emancipation; CNPQ::CIENCIAS HUMANAS::EDUCACAO